The impact of social media on secondary school students’ english language performance in Malaysia - Tillashini, Sathiyaseelan (2021)
The current teaching and learning system has incorporated internet into it. Internet has been playing a vital role in lives of many and now includes the younger generation. Learning through social media has its own impacts to its learners. However, Malaysia has not completely brought it into action because there are not significant studies that has proved the benefits of social media in the Malaysian context. Previous research mostly focused on one language skill which may not be sufficient to determine if social media does have an impact on student’s English language performances. The previous researches evolved around the same grades and only one type of social media which is inadequate. Emphasis in this study has also been given to evaluate the gender differences in the samples to determine the effectivity of social media as a whole. Implementing a quantitative method using the stratified random sampling in choosing the needed samples to carry out out an experimental research design where a pre-test and post-test is carried out to obtain results for this study. This study will serve as a reference to teachers in understanding how social media can contribute to English Language performances in classrooms. This study also contributes to the National Education Policy in terms of ICT in education which has few measures to undertake which is to enhance the use of digital technology for both students and teachers in its education system.